(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This paper explores in depth the microcosm set out by Salman Rushdie, in which the many perfomances of characters configure the bachtinian ‘pluridiscoursiveness’ as a simultaneous presence of multiples, metamorphic, voices.